Investigating incidence of bacterial and fungal contamination in shared cosmetic kits available in the women beauty salons - Leila Dadashi; Reza Dehghanzadeh (Tabriz University of Medical Sciences, 2016)
Background: Rich texture of cosmetics can provide a suitable medium for growth of pathogenic microorganisms. In addition, skin microflora of anyone is unique which might be harmful toanother person. Skin and eye pathogenicity could be communicated by sharing cosmetics in beauty saloons. The main objective of this study was to evaluate microbial contamination of in-use skin and eye cosmetics which are available as public make-up kits for women in the beauty salons. Methods: Fifty-two in-use skin and eye cosmetics were included in this cross sectional study.The specimens from all the cosmetics were collected following the owner's informed consent,and then about 1 g of the cosmetics was added to nine ml of liquid Eugon LT100 broth medium,two for each product. Ten beauty salons randomly selected from different regions of Tabriz city between June and August 2016. Cosmetics were sampled and carried to the laboratory in sterile condition and then examined to determine bacterial and fungal species in the samples. Results: All of in-use cosmetic were contaminated with bacteria (95% CI = 93.1%-100.0%) and about 19.2% by fungus and yeast (95% CI = 10.8%-31.9%). Streptococcus spp., Pseudomonas spp., Acinetobacter, Bacillus spp., Staphylococcus spp., Escherichia coli, Salmonella, Klebsiella,Citrobacter, Rhodotorula and Candida were dominant species which were isolated from the cosmetics. Powders with 38.5% (95% CI = 17.7%-64.5%) and eyeliners with 30.0% (95%CI = 6.7%-65.2%) were the most fungal contaminated products. Conclusion: Shared cosmetics in beauty salons are almost contaminated by bacteria and fungus.Therefore, it is suggested to avoid sharing cosmetics by women and prevent use of public cosmetics in toilet saloons.